Robust topology construction method with radio interface constraint for multi-radio multi-channel wireless mesh network using directional antennas - Xuecai Bao; Longzhe Han; Chengzhi Deng; Hai Zhang; Wenqun Tan (International Journal of Distributed Sensor Networks, 2016)
Multi-radio and multi-channel wireless mesh networks using directional antenna (MR-MC DWMN) greatly improve the spatial reuse of wireless channels and increase network capacity. However, the number of directional radio interfaces in MR-MC DWMN affects topology reliability and survivability. This article focuses on the construction of robust topology with radio interface constraints in MR-MC DWMN. Because of the limitation of the number of directional radio interfaces, we first formulate this topology optimization problem with directional radio interface constraints to be equivalent to establish k -connected topology with node degree constraints and then propose a robust topology construction algorithm with directional radio interface constraint. We define the link weight based on node degree and then use graph theory to construct the robust topology with node degree constraints. The proposed constructing robust topology with directional radio interface constraint can not only establish k -connected topology but also minimize the maximum node degree and meet the requirement of radio interface constraints. Simulation shows that constructing robust topology with directional radio interface constraint obtains less maximum node degree and average path length than existing k -connected topology control algorithms under the limitation of directional radio interfaces. Moreover, the constructing robust topology with directional radio interface constraint achieves better network performance than other algorithms.